Mental health services in local jails: report of a special national workshop - Dunn, Christopher S.; Steadman, Henry J. (DHHS publication, 1982)
The Special National Workshop on Mental Health Services in Local Jails : background and development / Christopher S. Dunn -- On "demons" and "gaols" : a summary and review of investigations concerning the psychological problems of jail prisoners / John J. Gibbs -- Service delivery models : a summary of examples / Carole H. Morgan -- Providing mental health services to jail inmates : legal perspectives / Richard G. Singer -- Psychological assessment in jails : implementation of the standards recommended by the National Advisory Commission on Criminal Justice Standards / Edwin I. Megargee -- Intervention models for mental health services in jails / Stanley L. Brodsky -- Juveniles in jail : special issues for a population subgroup / Donald A. Rademacher -- The labeling and treatment of mental illness in jails : a theoretical discussion / Walter R. Grove -- Jails and mental health : suggestions toward a research agenda / Don M. Gottfredson -- A research agenda for mental health services in local jails / Henry J. Steadman -- Workshop themes and subsequent activities / Christopher S. Dunn and Phyllis Jo Baunach.